Identification of delayed diagnosis of paediatric appendicitis in administrative data: a multicentre retrospective validation study. Issue 2 (28th February 2023) - Michelson, Kenneth A; Bachur, Richard G; Dart, Arianna H; Chaudhari, Pradip P; Cruz, Andrea T; Grubenhoff, Joseph A; Reeves, Scott D; Monuteaux, Michael C; Finkelstein, Jonathan A
Abstract : Objective: To derive and validate a tool that retrospectively identifies delayed diagnosis of appendicitis in administrative data with high accuracy. Design: Cross-sectional study. Setting: Five paediatric emergency departments (EDs). Participants: 669 patients under 21 years old with possible delayed diagnosis of appendicitis, defined as two ED encounters within 7 days, the second with appendicitis. Outcome: Delayed diagnosis was defined as appendicitis being present but not diagnosed at the first ED encounter based on standardised record review. The cohort was split into derivation (2/3) and validation (1/3) groups. We derived a prediction rule using logistic regression, with covariates including variables obtainable only from administrative data. The resulting trigger tool was applied to the validation group to determine area under the curve (AUC). Test characteristics were determined at two predicted probability thresholds. Results: Delayed diagnosis occurred in 471 (70.4%) patients. The tool had an AUC of 0.892 (95% CI 0.858 to 0.925) in the derivation group and 0.859 (95% CI 0.806 to 0.912) in the validation group. The positive predictive value (PPV) for delay at a maximal accuracy threshold was 84.7% (95% CI 78.2% to 89.8%) and identified 87.3% of delayed cases. The PPV at a stricter threshold was 94.9% (95% CI 87.4% to 98.6%) and identified 46.8% of delayed cases. Conclusions: This tool accurately identified delayed diagnosis of appendicitis. It may be used to screen for potential missed diagnoses or to specifically identify a cohort of children with delayed diagnosis.